Pengaruh sense of humor guru terhadap minat belajar matematika pada siswa - Oktaviani, Fara Nenti; Firmansyah, Dani (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
This study aims to determine the effect of teachers' sense of humor on students' interest in learning mathematics. This research was conducted on October 22nd, 2022 at Madrasah Aliyah Maulidina Utama, Bantargebang, Bekasi City. This study was motivated by the perception of the majority of students who consider math teachers and subjects unpleasant. This research is quantitative research. The population in this study were students in grades X, XI, and XII of Madrasah Aliyah Maulidina Utama, Bantargebang, Bekasi City. The sample used was 30 students with the sampling technique, namely simple random sampling. The data collection technique was carried out using a questionnaire. The data analysis technique used is simple linear regression. Based on the results of the research that has been done, a significance value of 0.002 <0.05 is obtained, which means that there is an influence of the sense of humor variable (X) on the interest in learning mathematics variable (Y). Beside that, the coefficient of determination (R Square) of 0.293 is obtained, which means that the percentage of influence is 29,3%.